Achieving employee environmental performance through perceived organizational support towards the environment: a mediated-moderation analysis: A Mediated-Moderation Analysis - Retno Purwani Setyaningrum (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
Purpose – This study aims to examine the effect of perceived organizational support for the environment (POSE) on environmental performance, by considering the mediating role of organizational citizenship behavior for the environment (OCBE) and the moderating role of individual green values. Design/methodology/approach – This study used a quantitative approach with a sample of 215 respondents from manufacturing company employees and used purposive sampling technique. The data obtained were analyzed using conditional process analysis and SPSS-Process. Findings – The results of this study indicated that POSE had a positive effect on environmental performance and proved that this influence can be found through the mediating role of OBCE. Then, the individual green value moderated the effect of POSE on OCBE, and the indirect effect of POSE on environmental performance through OCBE. Research limitations/implications – The data in this study were only taken from one city in Indonesia in a cross-sectional manner; thus, it required research with longitudinal data to explore causality between variables. Practical implications – The findings of this study can be a consideration for managers in manufacturing companies to understand the importance of improving environmental performance in companies and what factors influence it. Originality/value – Research that uses POSE and OCBE as factors that determine environmental performance in manufacturing companies, especially in Indonesia, is still limited. In addition, this study also considers the moderating role of individual green values and contributes to provide an understanding of the importance of environmental aspects for companies.